Antiviral Therapy of Chronic Hepatitis B with Nucleotide Analogs - Liu, Zhihua; Cao, Hong; Hu, Jing (Anti-Infective Agents in Medicinal Chemistry, 2009)
In recent years, significant progress has been made in the treatment of chronic hepatitis B. Currently four nucleoside analogues (lamivudine, adefovir, entecavir, and telbivudine) are available for the treatment of chronic hepatitis B virus (HBV) infection. The oral nucleos(t)ide analogues are generally better tolerated than interferon, but when administered for lengthy periods, a major concern is the antiviral-resistant mutation of HBV. Lamivudine, the first approved nucleoside analogue for the treatment of HBV infection, has been shown to be effective in suppressing HBV replication, so to ameliorate liver disease and prolong treatment with lamivudine has been shown to reverse fibrosis and cirrhosis. Among the approved nucleos(t)ide analogues (NAs) for hepatitis B, lamivudine has the highest and entacevir the lowest resistant rate for HBV. Adefovir is effective in suppressing wild type as well as lamivudine-resistance mutants. Telbivudine is more potent than lamivudine in suppressing HBV replication. On the other hand, telbivudine is associated with high rate of resistance. Combination therapy has been recently developed in order to increase efficacy and to decrease the occurrence of viral resistance. However, so far few combinations have been evaluated. No combination therapy demonstrated greater benefit as compared with monotherapy in inducing a higher rate of sustained response. However, in lamivudine-resistant HBV-infected individuals combination therapy of lamivudine and adefovir is more effective than adefovir monotherapy. More potent drugs and new combinations together with the understanding of the mechanisms of resistance to therapy are important challenges to improve the efficacy of treatment and to reduce the global disease burden related to chronic hepatitis B.
Keywords: adefovir